Concept of health surveillance programme for workers exposed to respirable crystalline silica at present and in the past - Joanna Nowak-Pasternak; Beata Świątkowska; Agnieszka Lipińska-Ojrzanowska (Nofer Institute of Occupational Medicine, 2023)
In the paper authors present general assumptions of health surveillance programme concept for workers employed in respirable crystalline silica (RCS) exposure at present and in the past. There is no effective treatment for silicosis thus disease prevention is of paramount significance. For decades efforts of World Health Organization (WHO) and International Work Organization (ILO) have been focused on eliminating silicosis globally. Unfortunately silicosis is still one of the most lethal occupational diseases and the preventative programmes have not yet been successful. The authors identify main steps to complete an overview of RCS exposure and suggest lines of actions to be taken before launching the health surveillance programme. Introduction of the health surveillance programme would increase awareness of harmful health effects of the RCS exposure, emphasize the significance of preventive medical check-ups and early diagnostics of occupational diseases as well as the importance of using appropriate protective equipment. The programme development on a national level might be carried out with the cooperation of multiple backgrounds and institutions. This would allow for detailed planning, implementation, monitoring and effective evaluation of its results. Having a better and updated knowledge of silicosis epidemiology, early diagnostics, the possible sources of RCS occupational exposure and evaluation of undertaken preventive actions are crucial factors in disease prevention. The programme introduction would be of educational significance for all the stakeholders and the groups engaged in the project implementation, which would contribute to high effectiveness of the preventive activities and their improvement in the future. Med Pr Work Health Saf. 2023;74(4):341-6.